Noncircular chainrings do not influence physiological responses during submaximal cycling - Leong, C. H.; Elmer, S. J.; Martin, J. C. (International Journal of Sports Physiology and Performance, 2022)
Pedal speed and mechanical power output account for 99% of metabolic cost during submaximal cycling. Noncircular chainrings can alter instantaneous crank angular velocity and thereby pedal speed. Reducing pedal speed during the portion of the cycle in which most power is produced could reduce metabolic cost and increase metabolic efficiency.